Students' perceptions on the use of Mentimeter media in learning to write Descriptive Text - Ima Chusnul Chotimah; Dian Anik Cahyani (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2023)
Technology media use in teaching is needed to speed the transformation of knowledge to students. This research focuses on knowing the students' response to using Mentimeter as media in teaching writing descriptive text. This research used qualitative analysis studies with the case study approach. This research was conducted in SMP Islam Al Madinah Jombang. The variable observed in this study is students' perception of using Mentimeter learning media in learning English to write descriptions. The instrument used to collect the data is a close-ended questionnaire with 20 statements. Interactive data analysis models Miles and Huberman used to analyze the data; are data reduction, data presentation, and conclusion. The analysis shows that the Mentimeter media can help students in writing activities, especially descriptive text. It can be seen from the students' responses that Mentimeter has many features to comment on in writing, the students can get new knowledge from their friends' writing because all students can access it, and the students can practice writing descriptively based on the picture given. From the result of the questionnaire, most of the students agree with all the statements mentioned.